2020
DOI: 10.3390/rs12030464
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Evidence and Multi-Modal Fusion Network for Ground-Based Cloud Recognition

Abstract: In recent times, deep neural networks have drawn much attention in ground-based cloud recognition. Yet such kind of approaches simply center upon learning global features from visual information, which causes incomplete representations for ground-based clouds. In this paper, we propose a novel method named multi-evidence and multi-modal fusion network (MMFN) for ground-based cloud recognition, which could learn extended cloud information by fusing heterogeneous features in a unified framework. Namely, MMFN exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Method [9] has shown good results on both datasets. Methods [7,11] fuse multimodal meteorological data and CNN, and achieved accuracy rates of 87.90% and 88.63%, respectively.…”
Section: Classification Methods Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Method [9] has shown good results on both datasets. Methods [7,11] fuse multimodal meteorological data and CNN, and achieved accuracy rates of 87.90% and 88.63%, respectively.…”
Section: Classification Methods Experimentsmentioning
confidence: 99%
“…Method [4] 68.90% 75.61% Method [9] 81.14% 92.17% Method [7] 87.90% -Method [11] 88 Note. References [7,11] use the meteorological data in MGCD, and NRELCD does not contain meteorological data.…”
Section: Mgcd Nrelcdmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al used the multimodal ground-based cloud dataset (MGCD), the first one composed of ground-based cloud images and multi-modal information. MGCD was annotated by meteorological experts and ground-based cloud-related researchers as six cloud types and the clear sky [11]. Liu et al selected the FY-2 satellite cloud image dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the fine-tuned densenet model achieved good results [10]. Liu et al proposed a novel method named multi-evidence and multi-modal fusion network (MMFN) for cloud recognition, which can learn extended cloud information by fusing heterogeneous features in a unified framework [11]. Zhang et al presented LCCNet, a lightweight convolutional neural network model, which has the lower parameter amount and operation complexity, stronger characterization ability and higher classification accuracy than the existing network models [35].…”
Section: Introductionmentioning
confidence: 99%